Solar Radiation Components on a Horizontal Surface in a Tropical Coastal City of Salvador - Gomes, Leonardo Rafael Teixeira Cotrim; Marques Filho, Edson Pereira; Pepe, Iuri Muniz; Mascarenhas, Bruno Severino; de Oliveira, Amauri Pereira; de A. França, José Ricardo (Energies (Basel), 2022)
Renewable energy must be prioritized by humankind, mainly if there is an expected increase of 50% in energy consumption by 2030 and climate change scenarios are also confirmed. Urban areas consume 70% of the available energy on the planet. Brazil, the largest country in South America, concentrates more than 85% of its population in urban areas, facing a challenge to increase the renewable power plants in its energy matrix. This work presents the solar radiation components behavior for the city of Salvador to contribute with initiatives for the use of solar energy resource. Firstly, a radiometric platform was implemented to obtain direct measurements of global (EG) and diffuse (EDF) components of incoming solar radiation at the surface. The knowledge of EDF is an important requirement to support photovoltaic system projects, and there is no information on direct measurements of this component in the State of Bahia. The diffuse radiation measurement device (DRMD) was designed and built for this purpose. The measurements of solar radiation components performed in this research were submitted to a specific quality control, statistically analyzed and used to evaluate the performance of different empirical models to represent the behavior of EDF  in the tropical coastal city. The results demonstrate the potential to explore solar energy in the city of Salvador, with annual values of sunshine higher than 2200 h year−1 and average daily intensities of EG  and EDF  equal to 18.7 MJm−2day−1 and 7.35 MJm−2day−1,  respectively. The analysis of the diurnal cycle shows that EG in summer reaches a maximum of 4.2 MJm−2h−1 and in the rainy season it reaches a minimum of 3.7 MJm−2h−1, both at noon, and in summer the EDFh is 35% of the EGh and it is 46% in the rainy season.